Ultrafine food powders as clean-label flow additives - Kleinschmidt, Sebastian; Heide, Isa; Kleinschmidt, Thomas (Frontiers in Chemical Engineering, 2024)
The aim of this work was to demonstrate the potential of the concept of clean-label-capable flow additives. These are spray-dried food ingredients whose particle size is small enough (< 10 µm) to take over the function of classic flow additives such as highly dispersed silicas. Their acceptance by customers and consumers has been declining for years, as they are primarily mineral excipients that are becoming increasingly unpopular in foods. This poses major problems for the food industry, as many food powders have poor flow properties and handling problems. The idea of clean-label flow additives is to create an alternative to meet consumer demands and industry requirements.Using four different cohesive food powders as examples, the authors demonstrate the effectiveness of this concept. For this purpose, flow additives were prepared from low-concentration solutions in a laboratory spray dryer. Dry particle coating was carried out in a tumbling mixer for 30 min, after which the flow properties of the coated powders were determined using a Schulze Ring shear tester. The results show that a significant improvement in the flowability of cohesive food powders is possible by using these spray-dried flow additives. In addition, an anti-caking effect could be observed. There is still a need for optimization in the production of such flow additives in order to increase their economy and effectiveness. Overall, the concept of clean-label flow additives shows great potential.